Electromagnetically vibrated Solid-Phase Microextraction for the analysis of organic compounds. (11th February 2010) - Joo, Jin Chul; Reardon, Kenneth F.; Shackelford, Charles D.; Wilmetti, Joseph F.
A newly developed electromagnetically vibrated Solid-Phase Microextraction (SPME) device for extracting 1, 4-dichlorobenzene and toluene from aqueous matrices was evaluated in terms of sorption equilibrium time, precision, and detection level relative to three other more conventional extraction techniques involving SPME, viz., static, magnetic stirring, and fibre insertion/retraction. Electromagnetic vibration at 420 cycles/s was found to be the most efficient extraction technique and also did not detrimentally impact the sustainability of the extracting performance of the SPME fibre. Therefore, electromagnetically vibrated SPME may be a more powerful tool for rapid sampling and solvent-free sample preparation relative to other more conventional extraction techniques used with SPME.